The Effect of Implementing Fingerprint Absence and Leadership on Employee Work Discipline - Ablian, Andre Agus; Wandra, Novera; Maas, Isyuliardi; Bismark, O.P.; Putra, Mandra Adrika (CV. Strata Persada Academia, 2024)
This research analyzes the effect of implementing fingerprint attendance and leadership on employee work discipline at the Lolo Community Health Center, Kerinci Regency, Jambi Province. This type of research is quantitative research, like a survey. Employees of the Lolo Community Health Center, Kerinci Regency, and Jambi Province represented the population of this study. The sample used in this research was 39 people. To find out an overview of the application of fingerprint attendance and leadership towards employee work discipline at the Lolo Community Health Center, Kerinci Regency, Jambi Province. The research results revealed that the Respondent Achievement Level (TCR) for fingerprint attendance, with an average of 169.07 or 86.70, was in the good category, TCR for leadership with 152.36 or 78.13, was in the good category, and TCR for work discipline with an average of 154 .70 or 79.33 is in the good category. Fingerprint attendance has a significant effect on employee work discipline. Leadership has a significant effect on employee work discipline. The influence variable of the independent variable (fingerprint attendance, leadership) significantly influences the dependent variable (work discipline) simultaneously/together.